Satisfaction of patients and students at the Integrated Clinics of a Dental School - João Paulo de Carli; Maria Salete Sandini Linden; Micheline Sandini Trentin; Soluete da Silva Oliveira; Marcos Eugênio de Bittencourt; Luiz Renato Paranhos (Universidade Estadual de Campinas, 2015)
Aim: The objective of this questionnaire-based research was to evaluate the level of satisfaction of students and patients at the School of Dentistry of the University of Passo Fundo (FOUPF). Methods: The questionnaire was administered after the patient's care, as follows: first, the student explained the study purposes and methodology to the patient, the option of not participating and the full confidentiality of the information obtained. Patients were selected among those undergoing treatment at the Integrated Clinic I and II Disciplines (5th year of undergraduate dental course) between March and November 2010. Results: Satisfactory results were obtained, as most interviewed patients (49; 98%) considered the care given by FOUPF students as positive. Another important factor mentioned by patients was the use of individual protection equipment and biosafety measures adopted by the students; 98% (n = 49) of the patients affirmed that the students were properly wearing individual protection equipment. With regard to aspects that could be improved, 36.7% (n = 18) of interviewed patients mentioned the need to schedule appointments more than once a week, 12.2% (n = 6) felt the need to reduce waiting times for consultations, and 10.2% (n = 5) wanted to reduce appointment duration. As much as 98% of students (n = 49) declared being attentive to dentistry situations, 56% (n = 28) were satisfied with their technical aptitudes, and 96% (n = 48) mentioned enjoying helping patients. Conclusions: The care given to patients by FOUPF students is done well, not requiring significant changes.